A Fixed Point Theorem for Three Pairs of Mappings Satisfying Contractive Condition of Integral Type in Dislocated Metric Space. (28th December 2014) - Ur Rahman, Mujeeb; Sarwar, Muhammad
Abstract : The aim of this paper is to study a common fixed point theorem for three pairs of self-mappings satisfying a contractive condition of integral type in the setting of dislocated metric space. We notice that our established theorem generalizes the main result of Branciari (2002) in the context of dislocated metric space.